Ritual Pengobatan Tradisional Rawukeng (Tombak Setan) pada Suku Bugis di Desa Tumbudadio Kecamatan Tirawuta Kabupaten Kolaka Timur - Andi Sinarwati; Rahmat Sewa Suraya; Syahrun Syahrun (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2022)
Traditional healing is becoming increasingly concerning, yet it remains an alternative way to heal for the Bugis tribe in Tumbudadio Village. This study aims to understand the process, analyze the function, and uncover the inheritance pattern of rawukeng (demon's spear) healing in the Bugis tribe. This study is qualitative descriptive with data collection techniques including observation, in-depth interview, and documentation then analyzed using data collection techniques, data reduction, data presentation and conclusion/data verification. The results of the study show that rawukeng traditional healing is still maintained as a legacy from the ancestors of the Bugis tribe. The inheritance pattern is passed down through the family or genetics, participating in rawukeng traditional healing, learning healing techniques, and observing traditional rawukeng healing that is imitated during the implementation.